Experiment of Tamper Detection and Recovery Watermarking in Picture Archiving and Communication Systems - Siau-Chuin, Liew; Jasni, Mohamad Zain (Science Publications, 2010)
Medical images such as x-rays, ultrasounds and Magnetic Resonance Imaging (MRI) plays an important role in helping the physicians to diagnose a disease or body conditions. These images can be tampered with existing image processing tools that is easily available. The usage of security measures such as watermarking can protect the integrity of the images. Numerous watermarking schemes with basic security functions and even tampered image recovery are available. But there is no research on the experimentation of watermarking in the operational environment that involves Picture Archiving and Communication Systems (PACS). Approach: This study focused on the experiment of selected watermarking scheme running in a simulated Digital Imaging and Communications in Medicine (DICOM) compliant PACS environment. A tamper detection and recovery watermarking was applied to an ultrasound image. Image will then be transferred to another computer within the PACS. Transferred and non-transferred image were tampered in the exact manner. The effectiveness of the watermarking scheme is known by comparing its recovery rates between these two tampered images. Results: The result showed that both transferred and non-transferred image had the recovery rates of 100% and recovered areas were identical. Conclusion: The result of the experiment showed that the selected watermarking scheme remains effective in a PACS environment. Further development is needed for a program that embeds watermark into images before it is sent to the PACS archive server for storage. The watermarking scheme tested needs to be further improved to be reversible for better implementation in PACS.